درجة ممارسة القيادات الأكاديمية بجامعة الحدود الشمالية للقيادة الإبداعية: دراسة ميدانية - المدني، معن بن محمد (جامعة بغداد - مركز البحوث التربوية والنفسية, 2020)
هدفت الدراسة إلى التعرف على درجة ممارسة القيادات الأكاديمية بجامعة الحدود الشمالية للقيادة الإبداعية، والتي تعزى لمتغيرات (طبيعة العمل، جهة العمل، الجنس، سنوات الخبرة في العمل الإداري بالجامعة)، ولتحقيق هدف الدراسة استخدم الباحث المنهج الوصفي المسحي، وأعتمد على الاستبانة كأداة للدراسة، والتي تكونت من (40) فقرة شملت أبعاد (الحساسية للمشكلات، المبادرة، الأصالة، المرونة)، وقد تكونت عينة الدراسة من (240) شملت (وكلاء الكليات والعمادات المساندة، والموظفين لديهم) خلال الفصل الدراسي الثاني للعام الجامعي 1439/1440هـ، وأظهرت النتائج بأن درجة ممارسة القيادات الأكاديمية للقيادة الإبداعية جاءت بدرجة "أحيانا" وبمتوسط حسابي عام بلغ (3.31)، حيث جاءت المهارات مرتبة على النحو التالي (المرونة، المبادرة، الحساسية للمشكلات، الأصالة), كما بينت النتائج وجود فروق ذات دلالة إحصائية بين متوسطات استجابات أفراد عينة الدراسة تعزى لمتغير الجنس في بعد "المبادرة" لصالح الذكور. وفي ضوء النتائج أوصى الباحث بعدة توصيات كان أبرزها: - وضع نظام مرن وفعال للاتصال ما بين القيادات الأكاديمية وبين الوكيلات والموظفات لديهم. - تشجيع القيادات الأكاديمية على عمل زيارات لجهات مناظرة لتبني أساليب عمل جديدة ومبتكرة تسهم في تطوير مهارات الإبداع لديهم.
The study aimed to identify the degree of academic leader's practices at the University of Northern Border for creative leadership, which attribute to different variables (nature of work, employer, gender, years of experience in administrative work at the university). To achieve the goal of the study, the researcher used the descriptive approach survey. Therefore, the researcher used a questionnaire as a study tool, which consisted of (40) items that included dimensions (sensitivity to problems, initiative, originality, flexibility). The study sample consisted of (240) participants included (agents of colleges, and supporting deanships, and their employees) during the second semester of the academic year 1439/1440 AH. The results showed that the degree of creative leadership practice of the academic leaders came with a degree "sometimes" and with a general average of (3.31). On the other hand, the skills came as follows (flexibility, initiative, sensitivity to problems, originality). As indicated by results, there were statistically significant differences between the averages of the responses of the study sample due to the gender variable in the "initiative" dimension in favor of males. In light of the results, the researcher came out with several recommendations, most notably: • Establishing a flexible and effective system for communication between the academic leaders and their female agents and employees. • Encouraging academic leaders to make visits to their counterparts to adopt, to develop, and to innovate work methods that contribute to develop their creativity skills.
Keywords: التعليم الجامعي -- طلاب الجامعات -- القيادات الأكاديمية -- جامعة الحدود الشمالية -- القيادة الإبداعية